2000
DOI: 10.1021/bm005564+
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A and Its Biomaterial Monomer Derivatives Alteration of in Vitro Cytochrome P450 Metabolism in Rat, Minipig, and Human

Abstract: Bisphenol A (BPA) is a common structural component in a wide variety of biomaterial monomers. The effects of BPA and the following derivatives: bisphenol A glycidyl methacrylate (BisGMA), bisphenol A glycidyl diacrylate (BAGDA), bisphenol A ethoxylate dimethacrylate (BAEDM), bisphenol A dimethacrylate (BADM), and bisphenol A diglycidyl ether (BADGE) on mixed function oxidases (MFOs) are reported in this study. The rate of formation of metabolites from isoform-specific substrates for the MFOs (or cytochromes) C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…It was shown that BisGMA at concentrations >0.1 mM caused an extreme depletion of the intracellular GSH pool as well as apoptosis in HGF (Engelmann et al 2004). Moreover, it was found that BisGMA significantly influences the activity of cytochrome P450 (Cannon et al 2000). An elevated activity of this mitochondrial enzyme complex may by associated with an increase of the intracellular concentration of ROS, which subsequently deplete the cells’ pool of detoxifying glutathione (Engelmann et al 2004; Sapone et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that BisGMA at concentrations >0.1 mM caused an extreme depletion of the intracellular GSH pool as well as apoptosis in HGF (Engelmann et al 2004). Moreover, it was found that BisGMA significantly influences the activity of cytochrome P450 (Cannon et al 2000). An elevated activity of this mitochondrial enzyme complex may by associated with an increase of the intracellular concentration of ROS, which subsequently deplete the cells’ pool of detoxifying glutathione (Engelmann et al 2004; Sapone et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…BPA has also been reported to interact with drug-and steroid-metabolizing activity of rat (111), pig (112), and human hepatic cytochrome P450s (113,114) by inhibition of activities, although these were measured at high micromolar concentrations of BPA. For example, testosterone 16␤-hydroxylase and testosterone 2␣-hydroxylase activities were inhibited by BPA at 100 m (69 and 74%, respectively) (111).…”
Section: Metabolism Of Bpamentioning
confidence: 99%
“…In addition, BPA may elicit biological responses by activation of kinase cascades (e.g., MAPK [12]) and by exhibiting antiandrogenic [13,14] and/or antithyroid activity [15]. Other reports have suggested that BPA increased bioavailability of sex steroid hormones by disrupting metabolic degradation [16][17][18].…”
Section: Introductionmentioning
confidence: 99%